Systematic Diagnosis of Quality Defects in Concrete Electricity Poles Through The New Seven Tools - Ikrimah Hilal; Emmy Liona; Dito Ranova (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study investigates the root causes of quality defects in concrete electrical poles produced by PT. LMN using the New Seven Tools (NST) approach. The research employs a qualitative–descriptive case study to systematically identify, categorize, and analyze defect patterns arising from human, machine, method, material, and environmental factors. Data were obtained through field observation, interviews, and documentation, then processed using the NST framework comprising Affinity Diagram, Interrelationship Diagram, Tree Diagram, Matrix Diagram, Activity Network Diagram, and Process Decision Program Chart (PDPC). The findings indicate that lack of routine supervision and insufficient machine maintenance are the dominant causal factors driving product defects, with the Man and Machine categories scoring the highest in the Matrix analysis (18 and 17, respectively). Corrective actions prioritized include implementing regular inspection schedules, preventive maintenance programs, and environmental standardization to improve workflow efficiency and reduce defect rates. Furthermore, the Activity Network analysis identifies the evaporation process as the critical path contributing to extended production time, while PDPC results underscore the importance of balancing technical feasibility with cost-effective corrective strategies. The study concludes that the integration of human resource development, process standardization, and preventive maintenance can significantly enhance product reliability and align production performance with zero-defect manufacturing principles. This research provides both theoretical and practical contributions by validating the applicability of the New Seven Tools method for comprehensive quality improvement in the Indonesian manufacturing sector.